Third-order parametric down-conversion in tapered optical fibers: An exact theoretical treatment of conversion efficiency - Brunner, Carla M.; Chekhova, Maria V.; Joly, Nicolas Y. (Proceedings of SPIE - The International Society for Optical Engineering, 2024)
Sub-micron tapered fibers have been proposed to be a suitable platform for the implementation of third-order spontaneous parametric down conversion (TOSPDC). Starting with the derivation of expressions for quantized fields in optical fibers, we devise an exact theoretical treatment of the expected triplet generation rate.
CRIS-Team Scopus Importer:2024-07-26
Keywords: photon triplets; polarization entanglement; quantum optics; tapered optical fibers; TOSPDC; triplet generation